DESAIN DAN IMPLEMENTASI PROGRAMMABLE LOGIC CONTROLLER ZELIO SOFT2 PADA PROSES OTOMASI INDUSTRI PENGEPAKAN - Budiyanto, Maun; Prisda Oetari Sihombing, Krystin (Jurnal Teknologi dan Vokasi, 2023)
The industrial world optimizes time, labor and process efficiency in producing goods. The application of automation technology is expected to increase the amount of production quickly and precisely. One of the technologies used is Smart relay. In this study using the Zelio Soft2 PLC smart relay software which is used to design and simulate the ball packing automation process. There are two programming languages ​​provided by Zelio Soft2, namely ladder diagrams (LD) and function block diagrams (FBD). The ladder diagram is designed to simulate the ongoing process step by step, while the FBD shows the type and block diagram used in the process. The designed system utilizes push buttons (on/off), box sensors, tennis ball sensors and driving motors. The results showed that the program simulation worked as planned.